Women resident in a female student housing: verse and reverse of self-care - Tatiana Brusamarello; Débora Fegadoli; Liliana Maria Labronici; Maria de Fátima Mantovani (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2007)
Cancer is the most frequently occurring neoplasia among women worldwide, followed by cervix uteri cancer whose main agent is the human papilloma virus. This research had as general goal: get to know women's health self-care among female undergraduates who live in a public university housing in Paraná State/ Brazil. Specific goals were as follows: to survey the frequency of breast self-exam, of gynecologic appointments, of colposcopic exam; to identify sexual life-related activities, preventive methods concerning sexually transmitted diseases (STDs) and contraception. This study has a quantitative approach and was carried out with a sample of 71 women. Data were gathered by means of a questionnaire and descriptively analyzed. The analysis evidenced that women ranged 18 to 33 years of age; 71.83% can undertake breast self-exam but 86.36% are unwilling to do that. It was still evidenced that 24.19% did not undergo the colposcopic exam after they became sexually active; 87.32% said they were previously sexually active; 53.22% disclosed that they did not always use any preventive methods for STD and 33.87% reported that they did not use them through the sexual intercourse. It can be concluded that those female students have access to information, however they are not risk-aware to undertake self-care.